CCAUSES OF MISMANAGEMENT OF SCHOOL FINANCES IN MREWA DISTRICT SECONDARY SCHOOLS - MUZENDA, DR DENIAS (IJRDO- Journal of Educational Research, 2017)
This study sought to find out the challenges faced by school heads in the management of school finances in Mrewa District. The population comprised all the secondary schools in the district. Random sampling was used to come up with a sample of ten (10) schools from where 40 respondents were purposively selected. The study adopted the descriptive survey design and the questionnaire and interview were used as the research instruments for collecting data. The study established that most heads lacked the accounting literacy required for effective management of school finances, and that there was little or no supervision at all from the Ministry of Primary and Secondary Education finance department personnel on financial management issues. The study recommends that there should be capacity building programmes for heads of schools, deputy heads as well as members of the school development committees. The Ministry of Primary and Secondary Education should increase both announced and unannounced visits to schools to monitor the use of finances in the schools.